Traits with negative effects and their benefits for soft wheat (Triticum aestivum L.) breeding - S. B. Lepekhov (Вавиловский журнал генетики и селекции, 2016)
The presence of traits with negative effects for yield in breeding samples has forced breeders to reject them in the field. As a result, the risk of loss of valuable genotypes has appeared. In this article, it has been proposed that traits as these can serve as indicators of high adaptiveness of a variety if, in spite of their presence, the cultivar has high yield. The aim of the research was to assess the applicability of V.A. Strunnikov’s hybrid vigour hypothesis in soft wheat breeding. The experiment was conducted in 2010–2012 on the experimental field of FSSI Altai RIA. The object of research was a collection of 75 varieties and lines of bread soft wheat of different origin and groups of ripeness. Cultivars were evaluated for yield and eight more traits associated with yield. A retrospective analysis of yield from F2–F4 hybrid populations in 2010–2014 has been conducted for assessment of different methods of selecting parent pairs for crossing. It has been established that crossing two high-yield varieties and high-yield varieties that have a trait with a negative effect to the donor of this trait leads to highyield hybrid populations. In the latter case, high-yield hybrid populations that are less likely to be rejected by the 4th generation occur at higher rates.